The Role of Private Off Dock Terminals on Port Efficiency (A Study of Sifax Off Dock Nig, Ltd.) - Ibiama, K. A.; Ogola, D. B.; Akpufu, I. D. (International Journal of Engineering and Management Research, 2019)
This study examines the role of private off dock terminal in enhancing port efficiency in Nigeria; the purpose of the study is to examine the extent to which private off-dock terminals have contributed to the efficiency of ports in Nigeria with respect to cargo clearance and forwarding, questionnaires were administered and review has been carried out to obtain primary data collection. A total of 100 questionnaires were administered to respondents and related literatures have been used for secondary data. A survey design method was adopted for the study. The statistical tools employed in analyzing the analysis are simple percentage; tables and hypothesis were tested using chi-square. Based on the findings, private off dock terminal has not really impacted on Lagos port over the last five years based on the cargo volume handled by them. It also reveals that private off dock terminal is facing problem in its implementation in Nigeria such as the availability of railway connectivity and inadequate finance and also the inconsistencies of government policies in line with off dock operations. The findings also reveals that the cost of clearing cargo at terminal is high compared to main ports. To this end the study recommended that reductions of chargers on cargo clearance and terminal handling of cargoes should be looked into by private off dock owners, government should ensure railway connectivity form port to off dock terminals, policies should be enacted, which will ensure efficient operations of private off dock terminal in Nigeria.
This study examines the role of private off dock terminal in enhancing port efficiency in Nigeria; the purpose of the study is to examine the extent to which private off-dock terminals have contributed to the efficiency of ports in Nigeria with respect to cargo clearance and forwarding, questionnaires were administered and review has been carried out to obtain primary data collection.
Keywords: Inland Container Depots; Cargo Volume; Cargo Pricing; Port Efficiency